Mode transition from adsorption removal to bombardment removal induced by nanoparticle-surface collisions in fluid jet polishing - Xuechu Zhao; Liran Ma; Xuefeng Xu (Friction)
Abstract The effects of impacting particles from a jet of liquid on the removal of a surface material (on the impacted workpiece) were investigated. Experimental observations show that the cross section of the material removed changed from ‘W’-shaped to ‘U’-shaped as the size of abrasive particles was increased. Comparisons between removed material profiles and particle collision distributions indicate that the particle-surface collisions are the main reason for the material removal. The deduced number of atoms removed by a single collision implies that a transition occurs in the removal mode. For nanoscale particles, the polished surface is likely to be removed in an atom-by-atom manner, possibly due to the chemisorption of the impacting particles on the impacted surface. Contrarily, for the case of microscale particles, bulk material removal produced by particle bombardment is more likely to occur. The present mechanism of material removal for particle-surface collisions is further corroborated experimentally.